Disrespected neighbo(u)rs : cultural stereotypes in literature and film - Rosenthal, Caroline, 1969-; Volkmann, Laurenz; Zagratzki, Uwe, 1954- (Cambridge Scholars Publishing, 2018)
Neighbourly relations frequently position a ""self"" against an ""Other"". This is the case for both individuals and nations, and, indeed, within the various cultural groups of a nation. Our racial, ethnic, social, or gender identities are often created in demarcating ourselves by stereotyping the Other. Disrespect of the immediate neighbour based on stereotypical pre-conceptions and cultural biases may lie dormant for a long time and then, as shown in recent conflicts around the globe, suddenly surface due to changed economic and political conditions. Media, including films and fictional as we